2018
DOI: 10.1002/jcp.27757
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological changes in experimental polycystic ovary syndrome in female albino rats: Using either hemin or L‐arginine

Abstract: Polycystic ovary syndrome (PCOS), one of the important endocrine disorders affecting females in the reproductive age, is caused mainly by an abnormal oxidation status that subsequently causes inflammatory conditions. Thus, this study aims to examine the possible individual prophylactic effects of gasotransmitters, hemin, or L‐arginine in letrozole‐induced PCOS. Fifty adult female albino rats were used and separated into a control group, which received the vehicle; a letrozole‐induced PCOS group (L), which rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…HEM was freshly dissolved in 0.1 mol/L NaOH, and pH was adjusted to 7.4 with 0.1 mol/L HCl and diluted with saline to the required volume. HEM was prepared in darkness and protected from light . GP and L‐NNA were dissolved in distilled water, and ISO was dissolved in saline immediately before administration.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…HEM was freshly dissolved in 0.1 mol/L NaOH, and pH was adjusted to 7.4 with 0.1 mol/L HCl and diluted with saline to the required volume. HEM was prepared in darkness and protected from light . GP and L‐NNA were dissolved in distilled water, and ISO was dissolved in saline immediately before administration.…”
Section: Methodsmentioning
confidence: 99%
“…The ISO+HEM+L‐NNA group was administered HEM (25 mg/kg/day) i.p . and L‐NNA (25 mg/kg/day) orally for 5 days and ISO (150 mg/kg/day) i.p . on the 4th and 5th day with 24 h between the two doses.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study showed that a diet supplemented with L-arginine affected gene expression in the mTOR signaling pathway by suppressing the mRNA expression of cathepsin B and the 20S proteasome in the liver [ 52 ]. Our findings suggest that L-arginine can improve the oxidative state [ 53 ] and improve ovary development during sexual maturity. Homovanillic acid is related to tyrosine metabolism.…”
Section: Discussionmentioning
confidence: 76%
“…Increased HMOX1 mRNA levels correlate with a high BMI and insulin resistance, and may be a compensatory mechanism to reduce oxidative stress and inflammatory status in adipose tissue ( 47 ). In letrozole-induced PCOS rats, the administration of hemin ameliorated oxidative stress, reduced inflammatory responses, restored hormonal balance, normalized metabolic function, and improved ovarian function ( 48 ). Our study found that patients with PCOS with the AA or AG genotype of A-42G SNP had significantly higher E 2 , LH, FSH, LH/FSH ratio, TC, HDL-C, LDL-C, apoB, and/or apoB/apoA1 ratio than those with the GG genotype.…”
Section: Discussionmentioning
confidence: 99%